The influence of scoliosis and wheechair customisations in rear impact - Walsh, Jennifer C. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2009)
Considerable advances in wheelchair occupant frontal impact safety have been achieved, but further research in rear impact is required. Future analysis would benefit from more biofidelic representation of wheelchair occupants, including effects of postural deformities such as scoliosis. In this work, the development and validation of a Madymo baseline wheelchair and occupant model for rear impact analysis is presented. In the model, the BioRID rear impact dummy is seated in a rigid wheelchair without a headrest and subjected to a 10g rear impact pulse. Sled tests of this configuration were performed and used to provide validation data for the numerical model. A comparison of the kinematic model predictions with the high-speed video test data showed a good ability to reproduce the whiplash motion sequence. Furthermore, the model correlates with the experimental time histories with an average difference of 10%. The model is therefore considered a valid representation of a 50th percentile male occupant of a rigid wheelchair in rear impact.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin.